What's your anger type? - "Sacco, Peter Andrew" (New Delhi, 2010)
Anger is a normal human emotion just as sorrow and happiness. Unfortunately, most times anger is expressed in non-productive and unacceptable ways which society deems as inappropriate. However, the good news is that we all have the ability to control anger. But how? This book shows the way. Describing various types of anger, it identifies their causes as well as precipitating factors, and finally offers effective ways to manage them. The different types of anger are explained with various scenarios and beautiful illustrations.
Keywords: Anger